Decision Support System to determine students who are eligible to receive the scholarship of Indonesian Smart Card (KIP) By Using Fuzzy Sugeno - Nanda Jarti (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Smart Indonesia Card (KIP) Is a state guarantee card for the continuity of college by providing freedom of tuition fees, fees given to underprivileged students so that they can continue their education. The problem that occurs in the provision of kip scholarships is that it is difficult to analyze students who are entitled to receive the scholarship so that standard criteria are needed such as proof of kip card, photocopy of report card, certificate of graduation, photo of student's house and photocopy of family card so that the scholarship given is right on target for students who entitled to receive such assistance. This study uses the Sugeno method by taking the Max value (the highest value) and using the or operator. The benefits of this research can be used as a decision-making system.